Psychedelic training program development: lessons from the evolution of the EMBARK program - Brennan, William; Field, Melissa; Schon, Catherine; Inamdar, Amir; Kelman, Alex (Frontiers in Psychology, 2025)
The field of psychedelic medicine is currently developing evidence-based standards and core competencies for training providers who offer psychedelic treatments. This article contributes to this effort by describing the iterative development of the EMBARK training program. This program has been developed by Cybin, Inc. for training session monitors in clinical trials of psychedelic treatments. The EMBARK training program has been used in two successfully completed clinical trials and three ongoing trials. This article details each of the three phases of the EMBARK training program’s development, including their core components, what worked well, lessons learned, and the rationale for any changes made. Innovations included in EMBARKCT, the most recent iteration of the training used in Cybin’s Phase 3 trials, are also discussed. These innovations include the use of artificial intelligence (AI) with expert human oversight to identify the need for additional support and training for session monitors. Finally, recommendations and implications for the field are discussed in this article.